2015
DOI: 10.1016/j.njas.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The changes in physical, bio-chemical, physiological characteristics and enzyme activities of mango cv. Jinhwang during fruit growth and development

Abstract: Keywords:Enzyme activities sucrose metabolism physical bio-chemical physiological mango a b s t r a c tThe changes in the physical, bio-chemical and physiological characteristics, and enzyme activities of sucrose metabolism during growth and development in mango fruit cv. Jinhwang were investigated. Fruit was harvested at five stages i.e., 50, 80, 110 and 140 days after anthesis (DAA). Several changes in the fruits were analyzed. The physical parameters like the fruit weight, width and length increased through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 20 publications
8
18
0
Order By: Relevance
“…Also it can be noticed that Ewais is more sweetness and more nutritive due to its high content of reducing sugars (7.03 ± 0.12), non-reducing sugars (9.36 ± 0.04), antioxidant phenolic compounds (43.77 ± 0.97). These results were in harmony with those revealed by Ara et al (2014), Naz et al (2014), Kittur et al (2001), Sajib et al (2014), Rajwana et al (2010) and Wongmetha et al (2015), who studied mango fruits quality and its correlation with physico-chemical parameter of fruits.…”
Section: Results Insupporting
confidence: 89%
See 1 more Smart Citation
“…Also it can be noticed that Ewais is more sweetness and more nutritive due to its high content of reducing sugars (7.03 ± 0.12), non-reducing sugars (9.36 ± 0.04), antioxidant phenolic compounds (43.77 ± 0.97). These results were in harmony with those revealed by Ara et al (2014), Naz et al (2014), Kittur et al (2001), Sajib et al (2014), Rajwana et al (2010) and Wongmetha et al (2015), who studied mango fruits quality and its correlation with physico-chemical parameter of fruits.…”
Section: Results Insupporting
confidence: 89%
“…Ellong et al (2015) revealed that firmness, taste, and pH properties correlated with mango varity, as well as starch, carbohydrates fractions, carotenoids, phenolic compounds, vitamins C and E contents. Wongmetha et al (2015) stated that sucrose metabolism and starch storage in mango were depended on growth stage, development in mango fruits, decrease activity of sucrose phosphate syntheses, acid invartase (AI) and neutral invartase (NI). Faria et al (2016) revealed that the content of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn, Zn and Na concentration in mango leaves as well as total chlorophyll, contents of a and b were depended on treatment strategies, growth stages and time of sampling.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrated that fruit firmness tended to decrease after 200 DAA, after reaching maturity. Similar results were found by Wongmetha et al (2015), in mango cv. Jinhwang (M. Indica L.) coming from Pintung (Taiwan), during the fruit development, with higher firmness from 50 DAA (5.35 kgf) to 110 DAA (25.9 kgf), followed by a decrease up to full maturity at 140 DAA (8.05 kgf).…”
Section: Changes In Mass Diameter Firmness and Soluble And Total Psupporting
confidence: 90%
“…Subsequent sucrose metabolism yields glucose and fructose, which contribute to increased concentration of total soluble sugars during ripening, as observed during ripening of other mango varieties (Wongmetha et al 2012) and apples (Núñez-Gastélum et al 2015). Sucrose is synthesized by sucrose phosphate synthase, an enzyme which has been shown to increase this disaccharide's concentration in mango, even when other enzymes concomitantly hydrolyze it (Wongmetha et al 2015), similar to the behavior found in our samples.…”
Section: Total Phenolics and Antioxidant Capacitysupporting
confidence: 85%